2003
DOI: 10.1179/135100003125001242
|View full text |Cite
|
Sign up to set email alerts
|

Protection against cisplatin-induced nephrotoxicity by Cu(II)2(3,5-diisopropylsalicylate)4

Abstract: The ability of Cu(II)(2)(3,5-diisopropylsalicylate)(4), CuDIPS, which exhibits superoxide dismutase (SOD)-like activity, to prevent cisplatin-induced nephrotoxicity was examined in rats. Rats were divided into four groups and treated as follows: (i) vehicle control; (ii) cisplatin (16 mg/kg, intraperitoneally); (iii) CuDIPS (10 mg/kg, intraperitoneally); and (iv) cisplatin plus CuDIPS. Rats were sacrificed 3 days post-treatment. Cisplatin alone resulted in significantly increased plasma creatinine and urea. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Moreover, it has also been found that cisplatin induces glutathione depletion, which is an important factor in nephrotoxicity (Zhang and Lindup, 1993). Supporting this hypothesis in a recent study, it has been suggested that cisplatin treatment causes a decrease in reduced glutathione content and activities of antioxidant enzymes (SOD, CAT, GSH-Px and GSH reductase) together with elevated TBARS levels in the rat kidney (El-Sayed and El-Masry, 2003). In a more recent study, it has been shown that cisplatin administration causes lipid peroxidation and impaired antioxidant enzyme activities in rat kidney (Ulubas et al, 2003).…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, it has also been found that cisplatin induces glutathione depletion, which is an important factor in nephrotoxicity (Zhang and Lindup, 1993). Supporting this hypothesis in a recent study, it has been suggested that cisplatin treatment causes a decrease in reduced glutathione content and activities of antioxidant enzymes (SOD, CAT, GSH-Px and GSH reductase) together with elevated TBARS levels in the rat kidney (El-Sayed and El-Masry, 2003). In a more recent study, it has been shown that cisplatin administration causes lipid peroxidation and impaired antioxidant enzyme activities in rat kidney (Ulubas et al, 2003).…”
Section: Discussionmentioning
confidence: 89%